Pengendalian Persediaan dan Waktu Tunggu Pengiriman pada Perusahaan Online Store di Jakarta - Hutabarat, Lisva Monang; Mudjiardjo, Mudjiardjo; Sholihah, Sita Aniisah; Nofrisel, Nofrisel; Sundoro, Oni Yudo (Institut Transportasi dan Logistik Trisakti, 2023)
The purpose of the study is to determine the impact of direct and indirect contribution of inventory control and delivery lead time of PT. Jakarta Notebook service quality and employees’ performance. The main problem of the study was the inadequate warehouses’ inventory control which cause out of stock and re-order when customers place orders. It is due to slow and inaccurate employees’ services. Another problem was caused by the frequent delay of the goods delivery to customers that impact on the service quality. This research used a quantitative research method. This study took 36 employees of PT Jakarta Notebook from the warehouse operation division as the respondents. The data collection was carried out by distributing questionnaires and analysing the data using Partial Least Square. The results show that inventory control and lead time partially contribute to service quality and employees’ performance. The service quality contributes to employees’ performance and could mediate the contribution of inventory control on employees’ performance. However, the service quality has not able to mediate the lead time contribution on employees’ performance of PT Jakarta Notebook warehouse operational division.